Long-term evolution of patient-reported outcome measures in spinocerebellar ataxias - Jacobi, Heike; Tezenas du Montcel, Sophie; Bauer, Peter (Journal of neurology, 2018)
To study the long-term evolution of patient-reported outcome measures (PROMs) in the most common spinocerebellar ataxias (SCAs), we analyzed 8 years follow-up data of the EUROSCA Natural History Study, a cohort study of 526 patients with SCA1, SCA2, SCA3 and SCA6.
Gesehen am 20.02.2020